Serum and urine ANGPTL8 expression levels are associated with hyperlipidemia and proteinuria in primary nephrotic syndrome - Li, Yue; Liu, Qingju; Kang, Chengdong; Cui, Weijing; Xu, Zichuan; Zhong, Fu; Gao, Xia (BMC nephrology, 2021)
Background This study aimed to investigate the expression characteristics of ANGPTL8 in patients with primary nephrotic syndrome and its possible correlation with hyperlipidemia and proteinuria. Methods ANGPTL8 levels were determined using an enzyme-linked immunosorbent assay in 133 subjects with PNS and 60 healthy controls. Results Compared with healthy controls, subjects with primary nephrotic syndrome had higher levels of serum and urine ANGPTL8 ( P < 0.001). In primary nephrotic syndrome patients, serum ANGPTL8 was positively correlated with cholesterol (r = 0.209, P < 0.05) and triglycerides (r = 0.412, P < 0.001), while there was no correlation with 24 hUTP. Urine ANGPTL8 was positively correlated with high-density lipoprotein cholesterol (r = 0.181, P < 0.05) and was significantly negatively correlated with creatinine (r = − 0.323, P < 0.001), eGFR (r = − 0, P < 0.001) and 24 hUTP (r = − 0.268, P = 0.002). Interestingly, the urine ANGPTL8 concentrations in membranous nephropathy and mesangial proliferative glomerulonephritis pathological types were different. Conclusions Serum and urine ANGPTL8 levels in primary nephrotic syndrome patients were correlated with blood lipid levels and proteinuria, respectively, suggesting that ANGPTL8 may play a role in the development of primary nephrotic syndrome hyperlipidemia and proteinuria.